Inflammatory cytokine expression in Fabry disease: impact of disease phenotype and alterations under enzyme replacement therapy - Yuan, Yujing; Zhao, Yawen; Li, Fan; Ling, Chen; Wu, Yuan; Ma, Wei; Wang, Zhaoxia; Yuan, Yun; Hao, Hongjun; Zhang, Wei (Frontiers in Immunology, 2024)
Objectives: The aim of this study is to explore the expression of inflammatory cytokines (ICs) in Fabry disease (FD), the correlation between ICs and FD phenotypes, and the impact of enzyme replacement therapy (ERT) on IC expression. Methods: We recruited 67 FD patients and 44 healthy controls (HCs) and detected concentrations of the following ICs: interferon-γ, interleukin (IL)-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12P70, IL-17A, IL-17F, IL-22, tumor necrosis factor (TNF)-α, and TNF-β. We also analyzed the impact of ERT on IC expression in FD patients and the relationship between IC expression and sex, genotype, phenotype, disease burden, and biomarkers. Results: Most ICs were significantly higher in FD patients than in HCs. A number of ICs were positively correlated with clinical aspects, including disease burden (Mainz Severity Score Index [MSSI]) and cardiac and renal markers. IL-8 was higher in the high MSSI (P-adj=0.026*) than in the low MSSI. Conclusions: ICs were upregulated in FD patients, indicating the role of the innate immune process in FD etiology. ERT ameliorated FD-related inflammatory activation, at least to some extent. IC expression was positively correlated with disease burden and clinical markers in FD. Our findings indicated that the inflammatory pathway may be a promising therapeutic target for FD.